Implementasi model STAD untuk meningkatkan hasil belajar dan aktivitas siswa mata pelajaran IPS - Yuli Ifana Sari (Jurnal Teori dan Praksis Pembelajaran IPS, 2016)
Based on observations note that results for students of class VII-A SMP Negeri 17 Malang quite low. It can be seen from the average value of class VII-A to subjects IPS Geography 51.5. The results of this study were lower due to several factors one of which is learning is dominated by teachers. STAD is one model of cooperative learning that can train students to work together and allow students to be more active eg active students ask, do worksheets, and other tasks. This study aims to improve learning outcomes and student activity by clicking implement the model STAD. This type of research is the PTK, which consists of two cycles, each cycle consisting of planning, implementation, observation, and reflection. Retrieval of data conducted by observation and a written test. The experiment was conducted in classes VII-A SMP Negeri 17 Malang with the number of students 41 people, in the subject matter atmosphere. The results showed that the learning outcomes of students has increased. It can be seen from the percentage increase in the average value of the test end of each cycle is from the first cycle to the second cycle of each value is 61.15 and 77, as well as increasing   the value of learning outcomes at 15.85 from the first cycle to the second cycle. The achievement of learning outcomes is increased   in the second cycle is supported by a good learning activity. Where the percentage of achievement of student learning activities in the first cycle an average of 46% and increased to 70.4% in the second cycle. So it can be concluded that by implementing the model STAD can improve students' learning activities amounted to 24.4%.Keywords: Model STAD, Learning Outcomes and Student Activities. http://dx.doi.org/10.17977/um022v1i12016p045